The Use of Acoustic Materials for Moveable Silence Booth to Support Remote Work in Office Facilities - Nabilla Retnaning Dewanti; Titi Indahyani; Cristella Natania; Meily Caroline Handi; Verencia Clarissa Sipasulta (International Journal of Architecture and Urbanism, 2026)
Acoustic elements are one of the most important factors to consider when designing a space, particularly in public spaces. This paper discusses the optimal design of the soundproof panels utilized in the moveable silence booth to support office facilities. The study aims to facilitate remote employees who do remote work as an effect of the prolonged pandemic era worldwide. This is one of the main issues with office furniture and interior design, where it is essential to have a space that can accommodate acoustic activities such as online meetings. When addressing these problems, it's essential to consider acoustic challenges, especially in a moveable silence booth or other chambers for online meetings individually that utilize acoustic components. The acoustic panel material study case also examined some values that can be highlighted through specific research stages (literature study, online observation, and online interviews) and design stages (design concept and final implementation). The result shows that the use of acoustic panels and sound insulation tempered glass in supporting moveable silence booth design can enhance the effectiveness and productivity of the users. The conclusion states are in terms of soundproofing elements can be a solution for designing a private booth in the office.